Online sentiment on Malaysia my second home (MM2H) rules tightening: A content analysis on popular social media news posts - Tang, Jieyee (2022)
The Malaysia My Second Home (MM2H) is a programme launched by the Malaysian government in year 2020. It is opened for any foreigners who are able to meet the requirements as stated by the government. However, it has been suspended twice due to different reasons. The MM2H programme has been reopened again in October 2021 with stricter rules. The recent changes further incite confusion and fuel the controversy. People from different background and races have left their comments, opinions, and feedback towards this issue publicly on the social media. Therefore, content analysis is used in this study to investigate the sentiments and emotions of the public towards this issue. This is because content analysis is useful in studying the change in public opinions and it is also a tool to understand the societal focus. Hence, it can play a role in helping the government, policy makers and the researchers to study further about the sentiments and emotions of the public on this issue. A total of 368 comments have been collected from popular Facebook posts published by famous news platform such as The Star, NST Online, Free Malaysia Today and The Straits Times. These samples are categorised into three sentiments which include positive, negative, and neutral sentiments. At the same time, they have been further classified into 7 emotions including joy, sadness, disgust, anger, surprise, fear, and neutral. Only one sentiment and one dominant emotion will be captured for each comment. This study concluded that 83.48% of the comments are negative and 58.86% of the comments show the emotion of ‘disgust’. The results of the study clearly show that most of the people are dissatisfied with the policy change made by the government. The government or policymakers should consider taking similar approaches to study the public opinions in the future to help them formulating their policies.